Evaluating Usability during the Web Application Development Process - Valentim, Natasha Malveira Costa; Nascimento, Elizamary; Conte, Tayana Uchôa (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Usability is known as one of the key aspects for use quality of an application. The commonly adopted technologies for usability assessment can be divided into two broad categories: Inspection, in which inspectors examine aspects of the application to detect violations of usability principles; and Test, in which users interact with the application in search of usability problems. In this paper, we report a practical experience of two usability evaluations carried out during the process of developing of a web application, one before the implementation of the web application (usability inspection) and another after the application is ready (usability testing). The results show the possibility of companies evaluating usability before and after application implementation with low cost.